Human rights and media - Papademas, Diana (Studies in communications ;, 2011)
Volume 6 on "Human Rights and Media" introduces and analyzes the significant relationship and discourse of human rights and media. As agenda setters, framers and integral actors in human rights movements, various forms of media are analyzed by the contributing authors. News media, the press, television, cinema, photojournalism, the internet and other documentary forms are among the media investigated by the authors. Civil society dialogue, the rhetoric and ideology of human rights, the propaganda and media responsibility around such themes as war, genocide, ethnic division, nationalism, race, gender, child labor and disability are human rights themes addressed in this volume.